2018
DOI: 10.1111/cyt.12550
|View full text |Cite
|
Sign up to set email alerts
|

Cleaved caspase‐3 expression is a potential prognostic factor for endometrial cancer with positive peritoneal cytology

Abstract: Our results suggest that CC3 in peritoneal cytology samples is a poor prognostic factor in patients with endometrial cancers, especially non-endometrioid tumours. Immunocytochemical analysis of CC3 expression could potentially facilitate identification of patients with high-risk endometrial cancer with PPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Caspase-3, a cysteine protease, plays an important role in execution of apoptosis. The proteolytic cleaves pro-caspase-3, an inactive proenzyme, into its active form, called cleaved caspase-3, which is responsible for specific cleavage of large numbers of key cellular proteins involved in apoptosis [ 23 ]. In this study, we detected the role of GHR knockdown and sorafenib in caspase-3 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-3, a cysteine protease, plays an important role in execution of apoptosis. The proteolytic cleaves pro-caspase-3, an inactive proenzyme, into its active form, called cleaved caspase-3, which is responsible for specific cleavage of large numbers of key cellular proteins involved in apoptosis [ 23 ]. In this study, we detected the role of GHR knockdown and sorafenib in caspase-3 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have shown that preoperative neoadjuvant intraarterial chemotherapy can reduce the incidence of postoperative complications [20], but the effect 4…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have shown that preoperative neoadjuvant intraarterial chemotherapy can reduce the incidence of postoperative complications [ 20 ], but the effect of this chemotherapy regimen on the adverse reactions of EC patients remains unclear. Therefore, reducing the incidence of adverse reactions of patients is the key to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted depletion of Ki67 gene in the mouse gut epithelium did not result in any cell proliferation deficiency. Furthermore, cleaved-caspase 3 detection is a better prognostic marker than Ki67 staining in colorectal and endometrial cancers [59 , 60] . Recently, suppression of TRAF6 expression through overexpression of miR-146a resulted in deregulation of tumor cell proliferation in non-small cell lung cancer [61] .…”
Section: Discussionmentioning
confidence: 99%